MOLECULAR AND CELLULAR MECHANISM OF I TYPE ALLERGIC REACTION DEVELOPMENT. BASIS PRINCIPLES OF DIAGNOSTICS AND THERAPY - Popov, N.N.; Kurinna, E.G. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
Mainstages of formation and developing of allergic reactions of  I type were analysed. Properties and the role of each components of the immune reaction: allergens, reagines, must cells and basofils were described. Basis principles of diagnostics and therapy were demonstrated.